Vision system for strain measurement in tensile test of boron sheet metal - Nik Nurulhusna, Muhmed Razali (2016)
In modern technologies, the automobile industry has an increase demand for lightweight components, improved product performance, efficiency and increase safety. The specific measurement of critical material properties has been done to develop the manufacturing and design of these components. An experimental investigation is conducts to explore the accuracy of strain rate measurement in tensile test using vision system as a new method. Thus, there are three objectives being highlighted in order to solve this problem. The problem to calibrate the strain rate calculation had been created by using MATLAB meanwhile camera. Next, the implementation of image correlation between MATLAB and camera and strain rate of sheet metal was analyze in tensile test. The objectives above was achieved by implementing the vision system to obtained deformation image. Therefore, the strain rate measurements are more accurate by using vision system method. However, the camera calibrator application shows the camera parameter used in this experiment. MATLAB software are new type of implementation to calculate the strain rate when the images were started to deform. In conclusion, vision system is able to provide logical and useful displacement. From the result obtained, the strains value increases with respect to the incensement of waist and width of the specimen.